Bridging atomistic magnetism and coercivity in Nd-Fe-B magnets. (September 2018) - Tsuchiura, Hiroki; Yoshioka, Takuya; Novák, Pavel
Abstract: Coercivity in rare-earth permanent magnets depends on the size and shape of magnetic grains. Recent experimental studies have revealed that, however, atomic scale structures around the grain-boundaries of magnets also play a crucial role to determine their coercivity. In this paper, we construct an effective spin model for the Nd2 Fe14 B structure based on first-principles calculations to describe atomistic magnetization dynamics of the magnetic grains, incorporating the information of the electronic states of the system. We find that the Nd ions located on the surfaces of the grains may have planar magnetic anisotropy, and that they can cause coercivity reduction. Graphical abstract: